Metarhizium brunneum (Ascomycota; Hypocreales) Treatments Targeting Olive Fly in the Soil for Sustainable Crop Production - Yousef, Meelad; Alba-Ramírez, Carmen; Garrido Jurado, Inmaculada; Mateu, Jordi; Raya Díaz, Silvia; Valverde-García, Pablo; Quesada-Moraga, Enrique (Frontiers in Plant Science, 2018)
Soil treatments with Metarhizium brunneum EAMa 01/58-Su strain conducted in both Northern and Southern Spain reduced the olive fly (Bactrocera oleae) population density emerging from the soil during spring up to 70% in treated plots compared with controls. A model to determine the influence of rainfall on the conidial wash into different soil types was developed, with most of the conidia retained at the first 5 cm, regardless of soil type, with relative percentages of conidia recovered ranging between 56 and 95%. Furthermore, the possible effect of UV-B exposure time on the pathogenicity of this strain against B. oleae adults coming from surviving preimaginals and carrying conidia from the soil at adult emergence was also evaluated. The UV-B irradiance has no significant effect on M. brunneum EAMa 01/58-Su pathogenicity with B. oleae adult mortalities of 93, 90, 79, and 77% after 0, 2, 4, and 6 of UV-B irradiance exposure, respectively. In a next step for the use of these M. brunneum EAMa 01/58-Sun soil treatments within a B. oleae IPM strategy, its possible effect of on the B. oleae cosmopolitan parasitoid Psyttalia concolor, its compatibility with the herbicide oxyfluorfen 24% commonly used in olive orchards and the possible presence of the fungus in the olive oil resulting from olives previously placed in contact with the fungus were investigated. Only the highest conidial concentration (1 × 108 conidia ml−) caused significant P. concolor adult mortality (22%) with enduing mycosis in 13% of the cadavers. There were no fungal propagules in olive oil samples resulting from olives previously contaminated by EAMa 01/58-Su conidia. Finally, the strain was demonstrated to be compatible with herbicide since the soil application of the fungus reduced the B. oleae population density up to 50% even when it was mixed with the herbicide in the same tank. The fungal inoculum reached basal levels 4 months after treatments (1.6 × 103 conidia g soil−1). These results reveal both the efficacy and environmental and food safety of this B. oleae control method, protecting olive groves and improving olive oil quality without negative effects on the natural enemy P. concolor.